2018
DOI: 10.12697/akut.2017.23.07
|View full text |Cite
|
Sign up to set email alerts
|

Motor performance in patients with knee osteoarthritis after 8-week home exercise program

Abstract: On patients with knee osteoarthritis (OA) the muscle strength, gait and everyday activities performance capacity decreased, though patients care started many years before. Patients care includes supervised physio therapy sessions and home exercise performing. Research goal was to assess the improvement in patients with knee OA motor performance with home exercise program (HEP) 8-weeks before total knee arthroplasty (TKA). Hypothesis: 8-week HEP improve legs motor performance in patients with knee OA. Ten femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…2 A)). Following visual inspection, the high heterogeneity could have been driven by the results of Sokk et al 85 However, the high heterogeneity did not change after its removal ( Supplementary Material 8 ).
Fig.
…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…2 A)). Following visual inspection, the high heterogeneity could have been driven by the results of Sokk et al 85 However, the high heterogeneity did not change after its removal ( Supplementary Material 8 ).
Fig.
…”
Section: Resultsmentioning
confidence: 95%
“…Low angles: Pooled data from 7 studies 65 , 67 , 80 , 85 , 87 , 98 , 101 (506 participants) showed low-certainty evidence with medium effect for reduced isometric hamstring strength in individuals with knee OA compared to pain-free controls (SMD = –0.76, 95%CI : –1.32 to –0.21; I 2 = 86%, p < 0.00001 ( Fig. 2 A)).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations